Krystyna Z. Sieciechowicz (1948–2012) - Manitowabi, Darrel; Molohon, Kathryn T. (Anthropologica, 2013)
An original thinker, community-based scholar and ad vocate of the rights of indigenous peoples, Krystyna Sieciechowicz, Ph.D., left us on 22 March 2012 at the age of only 63 after a long battle with cancer. In this memorial, we share insights about her life, academic contributions and collégial influences.